Technology validation and transfer - Asamenew, G.; Beyene, H.; Haile, Aynalem; Negatu, W. (International Livestock Centre for Africa, 1993)
As farming in Ethiopia is heavily dependent on animal traction, technologies that are based on this power source were envisaged to be appropriate for better management of Vertisols. Hence, the Joint Vertisol Project (JVP) began research on improved Vertisol technology that included 1) the use of an animal-drawn broadbed maker (BBM) to facilitate surface drainage and 2) the use of appropriate seeds, fertiliser and early planting. The aim of the technology verification and transfer were to verify the economic viability and acceptability of the BBM/Vertisol technology package and to popularies the technology so as to encourage large-scale adoption. A comparison of economic returns from crop grown with Vertisol technology package and traditional methods in selected Ethiopian highlands.